2000
DOI: 10.3109/00016340009169250
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of sonographic texture of the endometrium in post-menopausal bleeding a guide to further management

Abstract: This study adds the dimension of abnormal echogenecity of the endometrium to the currently followed criterion of endometrial thickness with a view to enhance accuracy, both for a better prediction of atrophy and a higher prediction for endometrial cancer. Expectant management can be offered to patients with a homogeneous endometrium which is 6 mm thick or less. Aggressive evaluation for a malignancy must be made if there is a focal increased echogenecity or a diffuse increased echogenecity even in a thin endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 11 publications
1
18
1
2
Order By: Relevance
“…In the present study age range was 41-70 years while in study done by Wong SF et al, Sousa R et al, Bharani B et al, and Sheikh M et al it was 38-94, 43-82, 52-65, 42-84 years respectively. [5,6,7,8] Mean age in the present study was 53.22 years while it was 47.43 to 56.5 years in other studies. 9 It was also observed that as the age of our subjects increased the incidence of postmenopausal bleeding decreased, indicating an inverse relationship between age and age of postmenopausal bleeding.…”
Section: Discussioncontrasting
confidence: 56%
“…In the present study age range was 41-70 years while in study done by Wong SF et al, Sousa R et al, Bharani B et al, and Sheikh M et al it was 38-94, 43-82, 52-65, 42-84 years respectively. [5,6,7,8] Mean age in the present study was 53.22 years while it was 47.43 to 56.5 years in other studies. 9 It was also observed that as the age of our subjects increased the incidence of postmenopausal bleeding decreased, indicating an inverse relationship between age and age of postmenopausal bleeding.…”
Section: Discussioncontrasting
confidence: 56%
“…Especially in patients with a suspected diagnosis of submucosal fibroids or endometrial polyps, the success of hysteroscopy on the diagnosis has been shown to be between 53-97%. 20,21 Hysteroscopic myomectomy should be considered firstline conservative surgical therapy for the management of symptomatic submucosal myomas. 22 It is highly effective in resolving abnormal bleeding, with a success rate between 70-90%.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, several studies showing that endometrial morphology assessment can be useful in the prediction of endometrial cancer 20 23 . Endometrial echogenicity and border in combination with ET has been shown to be a better predictor of endometrial cancer than ET measurement alone 21 23 . The best predictor of cancer at SIS is the finding of an irregular surface focal lesion (sensitivity 89% specificity 67%), Fig.…”
Section: Novel Techniques For Risk‐estimation Of Endometrial Malignanmentioning
confidence: 99%